2011
DOI: 10.1111/j.1365-2036.2011.04874.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the use of proton pump inhibitors and increased susceptibility to enteric infection

Abstract: SUMMARY BackgroundThe use of proton pump inhibitors (PPIs) is increasing worldwide. Suppression of gastric acid alters the susceptibility to enteric bacterial pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
302
1
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 426 publications
(329 citation statements)
references
References 107 publications
(89 reference statements)
13
302
1
13
Order By: Relevance
“…Most multivariate models fi nd advanced age, antibiotic use, co-morbidities, and longer hospital stays are independently predictive of CDI ( 211,214,232 ). Although several studies have not shown an association with proton pump inhibitors (PPIs) and CDI, many other studies have found an association ( 235,236 ). A meta-analysis of 29 studies of patients with CDI found that PPI increased the risk of CDI (pooled odds ratio = 2.15, 95 % confidence interval (CI) 1.81 -2.55) ( 234 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Most multivariate models fi nd advanced age, antibiotic use, co-morbidities, and longer hospital stays are independently predictive of CDI ( 211,214,232 ). Although several studies have not shown an association with proton pump inhibitors (PPIs) and CDI, many other studies have found an association ( 235,236 ). A meta-analysis of 29 studies of patients with CDI found that PPI increased the risk of CDI (pooled odds ratio = 2.15, 95 % confidence interval (CI) 1.81 -2.55) ( 234 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This prompted the FDA to issue a safety alert warning of C. difficile association with PPI use [92]. In addition to the associations with C. difficile infections, several links with enteric infections have been documented [93,94]. Respiratory infections such as community acquired pneumonia have been also linked to PPI use.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…For example, PPIs have been associated with Clostridium diffi cile ( 1,5 -9 ) and the US-FDA issued a safety announcement on PPI ( 10 ). In addition, there have been confl icting reports for pneumonia ( 11 -13 ) and other infections such as Salmonella and Campylobacter ( 14 ). However, the majority of studies exclude cases where a pre-existing GI infection To examine the incidence of Campylobacter and Salmonella infection in patients prescribed proton pump inhibitors (PPIs) compared with controls.…”
Section: Introductionmentioning
confidence: 99%